Integrated metabolomic, transcriptomic and network analysis elucidates therapeutic mechanisms of Ganoderma lucidum spore oil against granulomatous pulmonary nodules - Liu, Ya; Xu, Wendong; Wang, Kexin; You, Zhiye; Chen, Xiaohong; Ti, Huihui; Liang, Xiaoli; Cao, Lin; Cai, Hongfei; Liu, Juyan; Yang, Zifeng (Frontiers in Pharmacology, 2025)
Granulomatous pulmonary nodules represent a substantial health threat, with no available targeted therapies. Interventions based on medicinal plants approaches are pivotal for prevention and treatment. Ganoderma lucidum (GL) is a traditional botanical drug to treat inflammatory ailments. The spores of this fungus demonstrate distinct influences on immune response regulation, arthritis, and malignant growth inhibition. However, there is a lack of research on its application in the treatment of granulomatous pulmonary nodules. This study investigated the therapeutic potential and mechanism of G. lucidum spores (GLS) in mice with granulomatous pulmonary nodules. Utilizing granulomatous pulmonary nodules mice model induced by a peptide from the mycobacterial soda protein, we comprehensively evaluated the anti-granulomatous pulmonary nodules effects of GLS oil (GLSO) in vivo through various indices, such as lung micro-CT analysis, pathological conditions, inflammatory cytokine levels, chemokine. Metabolomics, transcriptomics, and network analysis were employed to elucidate its mechanisms. Results revealed that GLSO markedly reduced granuloma area and ground glass opacities in the lungs while attenuating pulmonary inflammation and chemokine levels. Metabolomic analysis identified 14 differential metabolites regulated by GLSO, including those involved in alanine, aspartate, and glutamate metabolism, arginine biosynthesis, and the tricarboxylic acid cycle. Transcriptomic and network analysis pinpointed the PI3K-Akt-mTOR signaling pathway as a central mechanism of GLSO action. Integrated analyses further indicated that GLSO alleviates granulomatous pulmonary nodules by inhibiting p-AKT and p-mTOR activation, thereby restoring metabolic balance and reducing inflammatory responses and chemokine secretion. These results position GLSO as a promising therapeutic candidate for granulomatous pulmonary nodules, acting through multifaceted regulatory mechanisms.